Analysis of A Tall Structure Using Staad.Pro Providing Different Wind Intensities as Per 875 Part-III - Prajapati, Sunil; Soni, Kapil (International Journal of Scientific Research in Civil Engineering, 2019)
In this research paper, the effect of wind velocity and structural response of building frame on sloping ground has been studied. Considering various frame geometries. Combination of static and wind loads are considered. For combination, 10 cases in different wind zones are analyzed. STAAD- Pro v8i software has been used for analysis purpose. Results are collected in terms of axial force, Shear force, moment, Storey-wise drift and Displacement which are critically analyzed to quantify the effects of various heights of structure.
Keywords: Staad.Pro; Structural Analysis; Storey Displacement; Bending Moment; Shear Force